MON-182 Increased Risk of Bleeding and Excessive Anticoagulation Using Standard Dose Low Molecular Weight Heparin (LMWH) in Cushing’s Syndrome - Haykal, Rasha (J Endocr Soc, 2020)
Background: Cushing’s Syndrome (CS) is a hypercoagulable state with increased risk of venous thrombosis events (VTE) including pulmonary embolism (PE) and deep venous thrombosis (DVT). In the absence of clear recommendations (1), a standard dose of low molecular weight heparin (LMWH) is given: 1 mg/kg q12h (with dose reduction for CrCl < 30ml/min and low BMI). Here we report an excessive level of anticoagulation (based on standard LMWH anti-Xa levels) using standard dosing requirements in 8 of 11 patients with CS complicated by VTE who received treatment with Enoxaparin. Methods: We retrospectively studied 6 women and 5 men with active hypercortisolism and VTE (6 PE and 5 DVT) treated with Enoxaparin given at doses below every 12 hours. Self-declared race/ethnicity were 7 white (one Hispanic), 2 unknown, 1 Asian, and 1 African. Anticoagulation therapy was monitored 4 hours after administration with measurement of LMWH anti-Xa (therapeutic range: 0.5-1.2 IU/mL). Results: The (subsequent) etiology of CS was ectopic ACTH secretion in 6 patients (3 pulmonary NET, 3 occult) and Cushing’s disease in 5. Median age was 53 years (range 24 - 74); median BMI 34.7 kg/M2 (range 24.9 - 52.9). Median urine cortisol was 659 mcg/24h (range 122 - 32,444; nl reference range 3.5 - 45). All had CrCl > 60 ml/min. 6 patients were taking a CYP3A4 inhibitor (Ketoconazole: n=5 or Mifepristone: n=1). 6/7 patients who received an initial dose of 1 mg/kg had supratherapeutic anti-Xa levels, from 1.4 - 2 IU/ml; five were on a CYP3A4 inhibitor. One died from a massive retroperitoneal bleed leading to organ failure. The other five required dose reduction; the median dose at which anti-Xa levels were at goal was 0.56 mg/kg (range 0.36 - 0.87 mg/kg). The sixth patient had an initial anti-Xa level of 0.2 IU/ml, which normalized on a dose of 1.1 mg/kg. One patient started at 1.3 mg/kg exhibited an anti-Xa level of 1.7 IU/ml, with appropriate anti-Xa levels at a dose of 0.6 mg/kg. 3 patients started at reduced treatment doses (0.68, 0.78 and 0.87 mg/kg) exhibited therapeutic anti-Xa levels. In summary, therapeutic anti-Xa levels were achieved at a dose of approximately 1 mg/kg in only three patients (0.87, 0.96, 1.12 mg/kg); others required reduction of the usual recommended dose to between 0.36 and 0.78 mg/kg. CYP3A4 inhibitors were used in 5/8 patients with elevated anti-Xa levels. Conclusions: Patients with Cushing’s syndrome appear to require lower than standard dose of enoxaparin; which may be only partly explained by concomitant CYP3A4 inhibitors. We suggest that anti-Xa levels be more closely monitored in CS patients to avoid morbidity and mortality caused by PE or bleeding. Further studies are needed to determine if this risk is present in patients receiving supraphysiologic doses of exogenous glucocorticoids. 1. Wagner J et al. Front Endocrinol (Lausanne). 9: 805, 2018